The Influence of Online Marketing, Brand Image and Purchase Decision on Customer Loyalty - Khotimah, Khusnul; Fitria, Lailani; Rafky, Rafnelly; Oktarina, Yolanda; Nofriadi, Nofriadi; Yani, Ahmad; Ali, Hapzi (Dinasti International Journal of Management Science, 2024)
The effect of online marketing, Brand image and buying decision on Customer loyalty is a scientific articlee in the literature study within the scope of the field of science. The purpose of this article is to build a hypothesis of the influence betweeen variables that will be used in further researrch. Research objects in online librariess, Google Scholar, Mendeley and othrer academic online media. The research method with the research library comes from e-books and open access e-journals. The results of this article: 1) Online marketing has an effect on Customer loyalti; 2) Brand image has an effect on Customer loyalti; and 3) purchasing decision has an effect on Customer loyalty.